Analysis of Micro-Holding of Leadership Ultra Package Manager - Purnama, Cantika Intan (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The strategy to ensure the success of Ultra Micro Holdings in realizing the spread, empowerment, growth and equity of the economy in Indonesia requires effective collective behavior to achieve the set targets. With that in mind in this study to determine and analyze the effectiveness of leadership style in Holding Ultra Micro. To answer the objectives of this research, a qualitative descriptive scientific method is needed. In this study, the SWOT data analysis method was used using the Internal Factor Evaluation (IFE) matrix and the External Factor Evaluation (EFE) matrix. From the results of data analysis using the SWOT analysis method, it can be seen that PT PNM's position in quadrant 1 (Aggressive) this position indicates that PT PNM has an opportunity, namely currently PT PNM's leadership is in good condition and can continue to improve quality. So PT PNM must maintain a transformational leadership style because it is appropriate and brings the company in good strength.